Hybrid cluster-based geographical routing protocol to mitigate malicious nodes in mobile ad hoc network. (2016) - Sudhakar, Sengan; Pandian, S. Chenthur
A mobile ad hoc network (MANET) consists of assorted mobile devices in a network without centralised administration and infrastructure. Routing processes in MANETs rely on cooperation of independent nodes constituting the network. Geographical Routing Protocols (GRPs) are suggested for MANETs in the literature. MANETs are highly susceptible to attacks. In this paper, a three-stage method has been proposed to address the performance degradation of a GRP due to the malicious nodes. This method based on a GRP, creates clusters. The malicious nodes are identified using modified hello message and secure keys are used to mitigate the effect of the maliciousness. The delay for the proposed clustered GRP was less than the GRP. When the size of the network increased, the end-to-end delay was significantly less. Cluster Heads (CHs) distribute public keys by using fuzzy logic. The effectiveness of the proposed cluster GRP when compared to the GRP is proved.